2018
DOI: 10.3892/or.2018.6813
|View full text |Cite|
|
Sign up to set email alerts
|

OBP‑801, a novel histone deacetylase inhibitor, induces M‑phase arrest and apoptosis in rhabdomyosarcoma cells

Abstract: Rhabdomyosarcoma (RMS) is an aggressive pediatric cancer of musculoskeletal origin. Despite multidisciplinary approaches, such as surgical resection, irradiation, and intensive chemotherapy, adopted for its treatment, the prognosis of patients with high-risk RMS remains poor. Thus, molecularly targeted therapies are required to improve patient survival and minimize side effects. Histone deacetylases (HDACs) modify transcription by deacetylation of the lysine residues in chromatin histone tails and several non-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 32 publications
3
11
0
Order By: Relevance
“…It is well known that HDAC inhibitors induce cell death such as mitochondria-mediated apoptosis in many cancer cells (17,18,20,34). Several reports have demonstrated that OBP-801 induces caspasedependent apoptosis in some cancers (24,35). In our study, rhabdoid tumor cell lines exhibited caspase-dependent apoptosis by OBP-801, like reported for other cancers.…”
Section: Discussionsupporting
confidence: 85%
See 4 more Smart Citations
“…It is well known that HDAC inhibitors induce cell death such as mitochondria-mediated apoptosis in many cancer cells (17,18,20,34). Several reports have demonstrated that OBP-801 induces caspasedependent apoptosis in some cancers (24,35). In our study, rhabdoid tumor cell lines exhibited caspase-dependent apoptosis by OBP-801, like reported for other cancers.…”
Section: Discussionsupporting
confidence: 85%
“…There are still challenges regarding the clinical application of OBP-801 in humans, because OBP-801 is a novel agent, and experimental data on its use in humans are scarce. However, in this study, the efficacy of OBP-801 was confirmed at a lower dose than previously used in our experiments on xenograft mouse models, and no serious adverse events were identified (24,35).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations